Simplified model for the calculation of degrees-day with variable time scale - Ovidio Rodríguez Santos (Universidad Central "Marta Abreu" de Las Villas, 2021)
In this paper, the authors propose a simplified model for the calculation of degree days for different time scales and variable base temperature. It is summarized in six expressions that result in a simple, compact and easy to program model in any spreadsheet. Its main advantage lies in the integrated calculation of degree days for daily, monthly and annual time scales, which makes it attractive for its application in strategic sectors of the economy such as the electro-energy, construction and agriculture sectors. It is applicable to regions for which the values of the regression coefficients necessary for the determination of the equivalent temperature (parameter defined by the authors, valid for a given geographical region) have been previously fixed. These coefficients have been determined for the areas surrounding the Yabú meteorological station, belonging to the province of Villa Clara, for the territory covered by this province and for the whole territory of the Cuban archipelago. Two versions of the model are presented, a base version and an extended one; the first one uses as input variables the mean temperature, the mean minimum temperature and the mean maximum temperature, according to the time scale to be considered, the second one allows its application by introducing the mean temperature as the only input variable. The difference in accuracy between these versions is not significant, so both are recommended